THE IMPORTANT SIGNIFICANCE OF ELECTROENCEPHALOGRAPHY IN THE STUDY OF BRAIN ACTIVITY (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article describes the main goal of the project aimed at improving the activities of psychologists in Uzbekistan, as well as the inclusion of the subject "psychophysiology" in the curriculum and its significant role in the practical activities of psychologists. The article shows the advantages of teaching psychophysiology as a basic subject in the training of psychologists in prestigious educational institutions on the example of other countries